Perancangan Bangunan untuk Meningkatkan Kualitas Hidup Penghuni: Analisis Dampak Ruang Terbuka pada Bangunan Perumahan di Kawasan Gajah Mungkur, Semarang Tengah - Kholil Fadli; Achmad Muchlis Ali; Miftahul Khairi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study analyzes the influence of open space on the quality of life of residents in the Gajahmungkur area, Central Semarang. A well-designed open space has a vital role in improving the physical, mental, and social wellbeing of residents. The results of the study show that effective open spaces can improve social interaction, health, and comfort of residents. However, many open spaces in this area have not been utilized optimally due to suboptimal design and improper location selection. Therefore, it is important to design open spaces that are environmentally friendly and well integrated to improve the quality of life of residents in the Gajahmungkur area.